Proceedings of the Seventh International Conference on Information and Communication Technologies and Development 2015
DOI: 10.1145/2737856.2737892
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone price as a proxy for socio-economic indicators

Abstract: Average mobile phone price of a region's residents has not been explored as a proxy variable for socio-economic indicators in development literature. Using handset models from mobile data logs of a telecom operator, we calculate average phone prices of subscribers at each cell tower, and then find their relationship with indicators from preexisting census data. Our results show that average phone price correlates well (absolute Pearson's correlation coefficient > 0.35 and p-value < 0.01) with indicators of acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…This is possibly due to numerous rural attendees visiting the State Foundation Day celebrations in Budapest or simply higher activity from individuals from groups of lower SES. In line with other research results [6,34] mobile phone prices as SES indicators are sufficient to uncover clusters in an urban population.…”
Section: Socioeconomic Status Clusterssupporting
confidence: 90%
See 2 more Smart Citations
“…This is possibly due to numerous rural attendees visiting the State Foundation Day celebrations in Budapest or simply higher activity from individuals from groups of lower SES. In line with other research results [6,34] mobile phone prices as SES indicators are sufficient to uncover clusters in an urban population.…”
Section: Socioeconomic Status Clusterssupporting
confidence: 90%
“…Using mobile phone prices as socioeconomic indicators have been proved to work well [6,34]. Sultan et al in identified areas where more expensive phones appear more often using indicators of accessibility to services, infrastructure, hygiene and communication.…”
Section: Socioeconomic Status Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Sultan et al identified areas in Jhelum, Pakistan, where the more expensive phones appear more often [31]. Using the same method, Budapest and its agglomeration were evaluated and the average phone prices were determined for every site based on the activity records.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the price and age of subscribers' mobile phones are proposed to be used as socioeconomic indicators. While Blumenstock et al used call history as a factor in socioeconomic status [30], Sultan et al [31] applied mobile phone price as a socioeconomic indicator and identified areas where more expensive phones appear more often; however, only manually collected market prices were used.…”
Section: Introductionmentioning
confidence: 99%